2010
DOI: 10.1002/tea.20380
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reflective discussions following inquiry‐based laboratory activities on students' views of nature of science

Abstract: This research investigated the effect of reflective discussions following inquiry‐based laboratory activities on students' views of the tentative, empirical, subjective, and social aspects of nature of science (NOS). Thirty‐eight grade six students from a Lebanese school participated in the study. The study used a pretest–posttest control‐group design and focused on collecting mainly qualitative data. During each laboratory session, students worked in groups of two. Later, experimental group students answered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 41 publications
0
29
0
10
Order By: Relevance
“…Overall, students' NOS views in this study became broader to include more than one scientific method, articulated the role of relevant evidence in more detail, and identified that the work of scientists involves complex interactions with other scientists (AAAS 1993;Osborne et al 2003;Yacoubian and BouJaoude 2010). The depth of the statements and the increased number of connections illustrate that students recognized a more complex view of science (Anderson 1981;Larkin et al 1980), which is supported by research that novice learners have fewer connections to draw on to understand concepts in context, while more expert learners can draw from more connections per concept (Hadwin et al 2011).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, students' NOS views in this study became broader to include more than one scientific method, articulated the role of relevant evidence in more detail, and identified that the work of scientists involves complex interactions with other scientists (AAAS 1993;Osborne et al 2003;Yacoubian and BouJaoude 2010). The depth of the statements and the increased number of connections illustrate that students recognized a more complex view of science (Anderson 1981;Larkin et al 1980), which is supported by research that novice learners have fewer connections to draw on to understand concepts in context, while more expert learners can draw from more connections per concept (Hadwin et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Khishfe and Lederman (2006) examined ninth-grade students' understanding of NOS and found that they improved in two conditions: NOS contextualized into environmental science and NOS decontextualized as stand-alone activities in the environmental science course. Yacoubian and BouJaoude (2010) found that sixth-grade students who participated in explicit and reflective discussions after inquiry activities improved their views of NOS, while students involved in implicit inquiry-based activities did not improve their NOS views. Much work has been done using general explicit and reflective instruction, and this study builds on this work by situating explicit NOS instruction in the forethought phase and reflective NOS instruction in the self-reflection phase of self-regulated learning strategies.…”
Section: Connection Between Explicit Reflective Nos Instruction Andmentioning
confidence: 92%
“…For example, instructional interventions designed to enhance epistemic change in learners have been designed and conducted in different subject areas such as physics (Kalman, Sobhanzadeh, Thompson, Ibrahim, & Wang, 2015); Karakostas & Hadzidaki, 2005), mathematics (Bielaczyc & Kapur, 2010;Liu, 2009;Mason & Scrivani, 2004), teacher education (Brownlee, 2003;DiPietro, 2004;Gill, 2004;Hong & Lin, 2010;Marra, 2005), or generally (Elen & Clarebout, 2001). Different strategies have been used, including epistemic games (Bielaczyc & Kapur, 2010), explicit reflection or discussion (Kalman & Rohar, 2010;Yacoubian & BouJaoude, 2010), and argumentation (McDonald, 2010). Very encouragingly, these studies all support Schraw and Sinatra's (2004) claim that "belief change can be brought about through wrestling with difficult issues" (p. 96) and instructional intervention.…”
Section: Concepts Epistemic Thinking and Conceptual Change In Learnmentioning
confidence: 90%
“…Enhancing learners' understanding of NOS is a longstanding goal of science education in general (e.g., Moore 1993; National Academy of Sciences 1998;Cobern 2000;Lederman 2004;McDonald 2010;Yacoubian and BouJaoude 2010). Part of the problem, however, is that scientists and philosophers of science themselves disagree about what exactly the nature of science is (Alters 1997;Abd-ElKhalick et al 1998;Rudolph 2000;Lederman 2004;AbdEl-Khalick 2005;Cho et al 2011;Duschl et al 2011).…”
Section: Insufficient/incorrect Factual Knowledgementioning
confidence: 92%